THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. INFOMEDIA NUSANTARA DIGITAL HELPDESK PERURI DIVISION SOUTH JAKARTA - Eti Ariyanti (International Journal Multidisciplinary Science, 2024)
This study aims to analyze the influence of motivation and work environment on employee performance at PT. Infomedia Nusantara Digital Helpdesk Peruri Division, South Jakarta. The research employs a quantitative method with an associative approach, focusing on two independent variables—motivation and work environment—and their impact on employee performance as the dependent variable. Data was collected through a survey of 58 employees using a closed-ended questionnaire. The results show that both motivation and work environment have a significant positive impact on employee performance, both partially and simultaneously. Motivation contributes 51.6% to the improvement of employee performance, while the work environment contributes 33.2%. Simultaneously, the two variables together account for 52.8% of the variation in employee performance, indicating that a combination of high motivation and a supportive work environment can significantly enhance employee performance. The study concludes that improving these factors can result in better organizational outcomes and provides recommendations for enhancing employee motivation and optimizing the work environment to foster productivity.